Negotiating Custom and Sharia: A Legal Review of the Bontowon Kon Bui’an Marriage Tradition in Bolaang Mongondow, Indonesia - Nurozi, Ahmad; Sobaya, Soya; Mamonto, Fikri Fachrurozi; Rohman, Moh. Fatkur; Arrozi, Fakhruddin (Al Irsyad: Jurnal Studi Islam, 2026)
The Bontowon Kon Bui’an tradition in Bolaang Mongondow raises concerns regarding symbolic kinship severance prior to endogamous marriage, which may appear to conflict with Islamic principles that emphasize the sanctity of family ties. This study evaluates whether Bontowon Kon Bui’an constitutes ‘Urf ?a??? or contradicts Sharia principles. Qualitative fieldwork was conducted through participant observation, semi-structured interviews with customary and religious leaders, and document analysis. Data were analyzed using ‘Urf, maq??id al-shar?’ah, and living law frameworks. The findings suggest that the symbolic severance of kinship functions as a ritualized mechanism rather than an actual breach of family ties. The practice aligns local social norms with Islamic expectations, with religious authorities demonstrating contextual tolerance provided the practice is recognized culturally rather than theologically. From the maq??id al-shar?’ah perspective, the tradition fosters communal harmony, prevents familial conflict, and reinforces family honor. These results indicate that local customs can coexist with Sharia when interpreted through appropriate normative frameworks, illustrating the adaptive and negotiated nature of Islamic law in pluralistic cultural contexts. In conclusion, Bontowon Kon Bui’an exemplifies how symbolic local customs can harmonize with Islamic law without violating core Sharia principles. This study provides insights for scholars, policymakers, and practitioners on integrating customary practices with Islamic law to preserve social harmony and cultural values.